Phycoremediation: Islamic value system toward environmental sustainability - Othman, Rashidi; Shaharuddin, Ruhul Izzati; Hj. Baharuddin, Zainul Mukrim; Hashim, Khairusy Syakirin Has-Yun; Ahmad Fadzillah, Nurrulhidayah (Springer Nature, 2018)
In Islamic value system, all the law and rules prescribed by Allah s.w.t. are our responsibility to fulfill as a servant. The matters through His guidances and laws are known as “Daruriyat Al-khams” which refers to the basic needs to ensure safety and continuation of humanity. These five basics are preservation of deen or religion (hifz al-din), life (hifz al-nafs), intellect and reason (hifz al-aql), lineage (hifz al-nasb), and wealth (hifz al-mal).The issues have been recorded by Ministry of Natural Resources and Environment, Malaysia generates 157,381.38 tones (8.37%) of heavy metals sludge annually. In 2014, 1,488,848 water pollution sources were identified. These sources included pollution from 3355 manufacturing industries, 10,795 sewage treatment plants, 1,276,195 Individual Septic Tank (IST), 3628 Communal Septic Tank (CST), 755 animal farm (pig farming), 531 agro-based industries, 879 wet markets, and 192,710 food services establishments. These industrial pollutants degrade ecosystem; pollute the water bodies, damage aquatic ecosystem, loss the soil fertility, and soil subsystem. In addition, only a small percentage (0.01%) of freshwater is available for human use, which comprises 3% of the total water on earth. Unfortunately, even this small proportion of freshwater is under immense stress due to rapid population growth, urbanization, and unsustainable consumption of water in industry and agriculture. Thus, we came out with a research to treat wastewater by employing algae to remove heavy metal, called phycoremediation in order to preserve sufficient clean and safe water toward a sustainable environment.